Prediction of Prognostic Factors and Genotypes in Patients With Breast Cancer Using Multiple Mathematical Models of MR Diffusion Imaging - Wang, Weiwei; Zhang, Xindong; Zhu, Laimin; Chen, Yueqin; Dou, Weiqiang; Zhao, Fan; Zhou, Zhe; Sun, Zhanguo (Frontiers in Oncology, 2022)
Purpose: To explore the clinical value of apparent diffusion coeffificient (ADC), intravoxel incoherent motion (IVIM), and diffusional kurtosis imaging (DKI) based on diffusion weighted magnetic resonance imaging (DW-MRI) for predicting genotypes and prognostic factors of breast cancer. Materials and Methods: A total of 229 patients with breast cancer confirmed by pathology were reviewed retrospectively. DWI, IVIM, DKI were performed in all patients. The corresponding ADC, true diffusion coefficient (D), perfusion-related diffusion coefficient (D*), perfusion fraction (f), mean diffusion rate (MD) and mean kurtosis value (MK) were analyzed. Results: D* and MK values were significantly higher in high-grade Nottingham group (NPI ≥ 3.4) than low-grade Nottingham group (NPI< 3.4). When D*≥ 30.95×10-3mm2/s, MK≥ 0.69, the NPI tended to be high grade (with AUCs of 0.712 and 0.647), respectively. The combination of D* and MK demonstrated the highest AUC of 0.734 in grading NPI with sensitivity and accuracy of 71.7% and 77.1%. Additionally, higher D*, f, MK and lower ADC, D values were observed in high Ki-67 than low Ki-67 expression group (P＜0.05). The AUC of the combined model (D+D*+f+MK) was 0.755, being significantly higher than single parameters (Z=2.770~3.244, P=0.001~0.006) in distingusing high from low Ki-67 expression. D*and f values in Luminal A subtype were significantly lower than in other subtypes (P<0.05). Luminal B showed decreased D value compared with other subtypes (P<0.05). HER-2 positive demonstrated increased ADC values compared with Luminal B subtype (P<0.05). Luminal A/B showed significantly lower D, D*, MD, MK than non-Luminal subtypes(P<0.05). The combined model ( D+D* +MD+MK) showed an AUC of 0.830 in diagnosing Luminal and non-Luminal subtype, which is significantly higher than single parameter (Z=3.273~4.440, P＜0.01). f ≥54.30% (OR = 1.038, P＜0.001) and MK≥0.68 (OR = 24.745, P=0.012) were resulted as significant predictors of Triple-negative subtypes. The combination of f and MK values demonstrated superior diagnostic performance with the AUC, sensitivity, specificity and accuracy of 0.756, 67.5%, 77.5% and 82.4%, respectively. Conclusion：the combination of these three models can improve the the diagnostic efficiency, and thus may contribute to opting an appropriate therapeutic approach in clinic treatment.